A contribution to the inventory and study of the impacts of phytophagous insects found on Baccharis halimifolia in its introduced range in France. (16th July 2013) - Fried, G.; Balmès, V.; Germain, J.‐F.
Abstract : Field surveys and a literature review were used to develop an initial inventory of phytophagous insects found on the invasive alien plant Baccharis halimifolia (Asteraceae) in its introduced range in France. A preliminary study provides the first quantitative data for the observed impact of Ceroplastes sinensis (Hemiptera: Coccidae) on the reproductive output of this invasive shrub.